Impact of nationwide COVID-19 lockdown on workload and injury patterns of major trauma cases in a regional trauma centre in Singapore - Min Li Kang; Woan Wui Lim; Daniel Jin Keat Lee; Jerry Tiong Thye Goo (Singapore Medical Journal)
Introduction: Singapore instituted lockdown measures from 7 February 2020 to 1 June 2020 in response to the coronavirus disease 2019 (COVID-19) pandemic. Methods: A retrospective analysis of cases from the national trauma registry was carried out comparing the lockdown period (from 7 February 2020 to 1 June 2020) to the pre-lockdown period (from 7 February 2019 to 1 June 2019). Data extracted included the volume of Tier 1 (injury severity score [ISS] >15) and Tier 2 (ISS 9–15) cases and epidemiology. Subgroup analysis was performed for Tier 1 patient outcomes. Results: Trauma volume decreased by 19.5%, with a 32% drop in Tier 1 cases. Road traffic and workplace accidents decreased by 50% (P < 0.01), while interpersonal violence showed an increase of 37.5% (P = 0.34). There was an 18.1% decrease in usage of trauma workflows (P = 0.01), with an increase in time to intervention for Tier 1 patients from 88 to 124 min (P = 0.22). Discharge to community facilities decreased from 31.4% to 17.1% (P < 0.05). There was no increase in inpatient mortality, length of stay in critical care or length of stay overall. Conclusion: There was an overall decrease in major trauma cases during the lockdown period, particularly road traffic accidents and worksite injuries, and a relative increase in interpersonal violence. Redeployment of manpower and hospital resources may have contributed to decreased usage of trauma workflows and community facilities. In the event of further lockdowns, it is necessary to plan for trauma coverage and maintain the use of workflows to facilitate early intervention.